EVALUASI RENDAHNYA PENYERAPAN ANGGARAN SATUAN KERJA PERANGKAT DAERAH DI PROVINSI RIAU TAHUN ANGGARAN 2012 - Andri, Alsar (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
Budget absorption is one indicator of the success of the regional work units in implementing the program, both the absorption realized in physical form or in the form of finance that are planned in a budget year. This will impact directly or indirectly on the economic growth of the region, because the policies that have been developed in the form of a program, a policy to improve the welfare of the community. This research was conducted using survey research methods, descriptive as well as their explanations level using qualitative data analysis. Results of the study, discuss the extent to which matters relating to budget preparation, budget discussions, management/budgeting and the factors that caused to low absorption of the Department of Industry and Trade of Riau Province in 2012.